Optimalisasi Dan Pengembangan Pemasaran Digital Pada UMKM Kalirungkut - Wahyu Dwi Arzaqy; Sumainah Fauziah (Universitas Katolik Widya Karya Malang, 2023)
With the rapid development of the era in the digital world, there are quite a lot of MSMEs, especially in Kalirungkut sub-district, which as a whole do not fully understand and know the rapid digital development so that the Group of 85 KKNT MBKM UPN